Production of tyrosinase defective mutants of Neurospora crassa - Angel M. Fuentes; Ian Connerton; Stephen J. Free (Fungal Genetics Reports, 1994)
We have produced mutants defective in tyrosinase activity using the RIP procedure (Selker et al. 1987 Cell 51:741-752, Marathe et al. 1990 Mol. Cell. Biol. 10:2638-2644). The tyrosinase gene has been shown to be a useful reporter in gene expression experiments (Kothe et al. 1993 FGN 40: 43-45). The availability of tyrosinase mutants will assist in these studies and will also be of use for future protein engineering experiments on tyrosinase (Fuentes et al. 1993 FGN 40:38-39)